Comparative Analysis of Mental Workload in Industrial Engineering Laboratory Assistants Using the NASA-TLX Method - Tajtibra, Firli; Putra, Perdana Suteja; Prihadianto, Rahaditya Dimas (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
The education system at Telkom University Surabaya (TEL-U SBY) is not only in the form of theory but also practicum material, one of which is like the activities in the Industrial Engineering Stdui Program at Telkom University Surabaya. In this Study Program has a laboratory unit as a means of practicum activities, which includes 5 laboratories. The practicum activities involve the role of active students who are responsible as laboratory assistants in the implementation of practicum. This makes them have two roles that can lead to the potential for increased mental workload (MW). So, in this study, a comparative measurement of the mental workload of laboratory assistants was carried out to help identify the level of workload experienced, as well as increase efficiency and productivity. The method used as an approach in measuring the mental workload of laboratory assistants is through the NASA-TLX method. The results obtained from this study, it is known that the Engineering Management laboratory has the highest mean score of 65.42 and the second highest is the Optimization and System Modeling laboratory of 60.56. The most dominant indicators as the cause of the mental workload of laboratory assistants are the effort and temporal demand indicators. Recommendations for improvement include task and time management, work appreciation, and improving adequate practicum facilities, for the comfort and satisfaction of laboratory assistant members.